Prevalence of dental fluorosis among 12-15-year-old students in Enugu Metropolis, Nigeria - Linda Oge Okoye; Osa-Eloka Christiandolus Ekwueme; Elizabeth O Sote; Benneth Tochukwu Amaechi (Wolters Kluwer Medknow Publications, 2019)
Background: Excessive ingestion of fluoride during tooth development, particularly at the maturation stage, may result in dental fluorosis, with clinical implications. Literature is scarce on dental fluorosis in Enugu, Nigeria. Purpose: The aim of this study was to assess the prevalence of dental fluorosis in Enugu, a major city in South East Nigeria. Materials and Methods: A multistage sampling technique was used to select a calculated sample of 400 students. A pretested interviewer-administered questionnaire was used to ascertain student's sociodemographic and related variables. The student participants were examined for dental fluorosis using Dean's index criteria according to the World Health Organization guidelines. Data were analyzed using SPSS version 16, and Chi-square test of association was used to compare proportions and ratios with significant level set at P < 0.05 and 95% confidence level. Results: Among the 400 students analyzed, 231 (57.8%) and 169 (42.2%) were male and female, respectively. Mean age was 13.43 ± 1.021 years. The prevalence of dental fluorosis was 11.3%, with the preponderance of very mild score (82.2%), and no observed severe dental fluorosis. The difference in the distribution of the scores of fluorosis among the children was highly statistically significant (χ2 = 72.80, P = 0.000). Dental fluorosis was found present in 39 (10.3%) of 378 users of fluoridated toothpaste and in 6 (27.7%) of the 22 users of nonfluoridated toothpaste. The differences in the presence and absence of dental fluorosis were statistically significant among users of fluoridated toothpaste. Conclusion: This study shows the prevalence of dental fluorosis to be low among secondary school students of Enugu metropolis.